2022
DOI: 10.1021/acs.jafc.2c01176
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid Inhibits Platelet Aggregation and Neointimal Hyperplasia In Vivo and Vascular Smooth Muscle Cell Dedifferentiation, Proliferation, and Migration In Vitro via Activation of the Keap1-Nrf2-ARE Antioxidant System

Abstract: The activation of platelets and proliferation of vascular smooth muscle cells (VSMCs) in the vascular intima play an essential role in the pathological mechanism of vascular restenosis (RS). Rosmarinic acid (RA) is a natural phenolic acid compound. However, its mechanism of action on platelets and VSMCs is still unclear. This study investigated the effects of RA on platelet function, VSMCs phenotypic conversion, proliferation, and migration in vascular remodeling with a specific focus on the Keap1-Nrf2-ARE sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…In addition, Chen et al found that RA could attenuate the lipopolysaccharide-provoked inflammatory response of VSMCs by inhibiting the MAPK/NF-κB cascade . Our previous work demonstrated how RA affects platelet functioning and intimal neogenesis in rats with carotid balloon injury; however, the exact mechanism is largely unknown. As a result, understanding the molecular mechanism underlying the suppressive impacts of RA on vascular remodeling may aid in the design of future preventive and therapeutic measures.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, Chen et al found that RA could attenuate the lipopolysaccharide-provoked inflammatory response of VSMCs by inhibiting the MAPK/NF-κB cascade . Our previous work demonstrated how RA affects platelet functioning and intimal neogenesis in rats with carotid balloon injury; however, the exact mechanism is largely unknown. As a result, understanding the molecular mechanism underlying the suppressive impacts of RA on vascular remodeling may aid in the design of future preventive and therapeutic measures.…”
Section: Discussionmentioning
confidence: 94%
“…A phenolic substance called rosmarinic acid is frequently found in a variety of plants from the Lamiaceae family, such as Comfreyaceae, Cucurbitaceae, Lindenaceae, and Apiaceae. , In addition to protecting vascular endothelial cells, RA has anti-inflammatory, antioxidant, and antiplatelet aggregation properties. It also has anti-inflammatory and antireperfusion-induced myocardial injury prevention properties. , Our previous study illustrated that RA inhibits platelet aggregation and intimal hyperplasia in the early stage of carotid balloon-injured rats and protects VSMCs stimulation in vitro . However, the mechanism underlying the effect of RA on neointimal hyperplasia is still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven known compounds were isolated and identified as 6’‐acetyl‐3,6,2’‐tri‐p‐coumaroyl sucrose ( 3 ), [13] 6′‐acetyl‐3,6,2′‐triferuloyl sucrose ( 4 ), [13] tiliroside ( 5 ), [15] afzelin ( 6 ), [16] quercitrin ( 7 ), [17] 2‐hydroxycinnamaldehyde ( 8 ), [18] cinnamic acid ( 9 ), [19] 3,4‐dimethoxycinnamic acid ( 10 ), [20] dehydrovomifoliol ( 11 ), [21] 4‐hydroxy‐3,5‐dimethoxybenzaldehyde ( 12 ), [22] and (S)‐(−)‐rosmarinic acid ( 13 ) [23] by comparison of NMR data with those reported in the literature (Figure 3). Among the previously reported compounds, 3 , 4 , 6–9 , 13 have been documented for their antiplatelet aggregation and anticoagulant activities [24–28] . Cinnamic acid ( 9 ) and its derivative, 2‐hydroxycinnamaldehyde ( 8 ), also had anticancer, [29,30] and anti‐inflammatory properties [31–33] .…”
Section: Resultsmentioning
confidence: 99%
“…Among the previously reported compounds, 3, 4, 6-9, 13 have been documented for their antiplatelet aggregation and anticoagulant activities. [24][25][26][27][28] Cinnamic acid (9) and its derivative, 2-hydroxycinnamaldehyde (8), also had anticancer, [29,30] and anti-inflammatory properties. [31][32][33] Additionally, 8 was found to contribute to the restoration of liver function in cases of acetaminophen-induced acute liver injury.…”
Section: Structure Elucidation Of Two New Compoundsmentioning
confidence: 99%